Cover Feature: Anomeric Stereoauxiliary Cleavage of the C−N Bond of d‐Glucosamine for the Preparation of Imidazo[1, 5‐a]pyridines (Chem. Eur. J. 29/2022). Issue 29 (26th April 2022) - Zeng, Kui; Ye, Jin; Meng, Xintong; Dechert, Sebastian; Simon, Martin; Gong, Shuaiyu; Mata, Ricardo A.; Zhang, Kai
Abstract : The Gänseliesel showcases the scientific magic in Göttingen ! Scientific magic on the α‐anomer of d ‐glucosamine helps the targeted cleavage of C−N bonds in d ‐glucosamine (α‐2° amine) from biobased resources and the conjunction of nitrogen in the synthesis of imidazo[1, 5‐a]pyridines. This new approach expands the scope of readily accessible imidazo[1, 5‐a]pyridines relative to existing state‐of‐the‐art methods. A key strategic advantage of this approach is that the α‐anomer of d ‐glucosamine enables C−N bond cleavage through a seven‐membered‐ring transition state. More information can be found in the Research Article by K. Zhang and co‐workers (DOI: 10.1002/chem.202200648 ).